2012
DOI: 10.1111/asj.12021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low protein diet and low protein diet supplemented with synthetic essential amino acids on meat quality of broiler chickens

Abstract: We investigated the effects of a low crude protein (CP) diet and a low CP diet supplemented with synthetic essential amino acids (EAA) on the meat quality of broiler chickens. Twenty-one-day-old chickens were assigned to one of three diets: control, low CP (LCP), or low CP supplemented with EAA (ELCP). The chickens received these diets for 10 days. The shear force value (SFV) and free glutamate content of the Pectoralis major muscle were measured as indicators of the meat toughness and taste. The collagen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Actually, the levels of FAA or AA in muscle were also influenced by multi-factors including breed, cross combinations, sex, different tissues, genotype, the level of dietary protein, and age (Mahan and Shield 1998;Morales et al 2011). These results were in accordance with previous reports that the composition of FAA or AA in muscle had similar tendency in pig, goat, impala, broiler chicken, and fish (Wesselinova 2000;Hoffman and Ferreira 2004;Webb et al 2005;Jiang et al 2011;Kobayashi et al 2013). Each animal body protein had its individual-specific amino acid composition, maintenance need, and turnover rate.…”
Section: Discussionsupporting
confidence: 90%
“…Actually, the levels of FAA or AA in muscle were also influenced by multi-factors including breed, cross combinations, sex, different tissues, genotype, the level of dietary protein, and age (Mahan and Shield 1998;Morales et al 2011). These results were in accordance with previous reports that the composition of FAA or AA in muscle had similar tendency in pig, goat, impala, broiler chicken, and fish (Wesselinova 2000;Hoffman and Ferreira 2004;Webb et al 2005;Jiang et al 2011;Kobayashi et al 2013). Each animal body protein had its individual-specific amino acid composition, maintenance need, and turnover rate.…”
Section: Discussionsupporting
confidence: 90%
“…Various organic acids (e.g., formic, citric, fumaric, malic, and benzoic) can improve growth performance and regulate the intestinal microbiota in pigs ( Partanen and Mroz, 1999 ; Piva et al, 2002 ; Kluge et al, 2006 ; Øverland et al, 2008 ; Halas et al, 2010 ). However, the strategy of using a low protein diet balanced with AAs has no influence on growth performance in commercial swine operations ( Opapeju et al, 2008 ) and broiler chickens ( Kobayashi et al, 2013 ). Our research goal was to examine how, while applying current production practices, a low protein diet (3% below normal) could be supplemented with AKG to improve growth performance, the microbial communities, and metabolic profiles in the cecum of a growing pig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains challenging to improve chicken meat quality while maintaining a high growth rate. Currently, wholesalers have acknowledged delicate flavor as an important indicator of meat quality [ 1 ]. Studies demonstrated that inosine monophosphate (IMP) confers the distinct flavor in the cooking process.…”
Section: Introductionmentioning
confidence: 99%